Descriptive Analysis of the Medical Consultations Conducted in the Dental School of Kerman University of Medical Sciences - Z Atai; N Navabi; SMR khoshroo; L Asadi (Islamic Azad University, 2017)
Background and Aim: Medical consultations have an important role in dental diagnosis and treatment planning, and are indicated for patients with uncertain medical histories. The purpose of the present study was to evaluate the medical consultations conducted for a group of patients in need of dental treatments. Materials and Methods: in this cross-sectional study, 173 medical consultation requests were reviewed at the diagnosis and oral medicine department of the dental school of Kerman University of Medical Sciences during 2014-2015. The demographic data, reasons for consultation, and medical precautions were descriptively analyzed. Results: The mean age of the patients was 37.3±6.5 years, and 64.2 % of the subjects were females. The main reasons for medical consultations were hypertension (28.9 %) and cardiovascular assessment (19.7%). The main dental concerns included the need for preoperative antibiotic prophylaxis (7.5%) and the use of local anesthesia without epinephrine (19.7%). Conclusion: Medical consultations reduce the medical risks associated with dental procedures and unnecessary antibiotic prophylaxis. Good communication between dentists and physicians is essential for satisfactory patient care